Geotechnical Planning for Slope Stability in Limestone Mining at PT Rahmad Makmur Abadi, Punggulrejo Village, Rengel District, Tuban Regency - Yudho Dwi Galih Cahyono; Alifer Zalfani Ardiansyah; Rinaldhie Guntur Dharmansyah; Avellyn Shinthya Sari; Gilberto Amaral (Journal of Earth and Marine Technology (JEMT), 2026)
This study focuses on optimal slope-geometry planning in the IUP area of Rahmad Makmur Abadi Ltd, Punggulrejo Village, Rengel District, Tuban Regency, to create a safe working environment and maximize material recovery. Slope stability is evaluated by analyzing the Factor of Safety (FoS ≥ 1.2) using the finite element method based on the Hoek–Brown failure criterion, as well as the Probability of Slope Failure (PF ≤ 10%) using Rosenblueth’s Point Estimate Method under the weakest slope conditions (saturated, with minimum UCS value), in accordance with KEPMEN ESDM No. 1827/K/30/MEM/2018. Through iterative geometric modeling (trial and error), the study produced recommendations for a single slope geometry (bench height of 20 m, width of 6 m, at a 90° inclination). It divided the overall slope into two blocks: Block 1 (bench height of 8 m, width of 4 m, at an 85° inclination with 9 benches, with the lowest bench at 7 m) and Block 2 (bench height of 8 m, width of 5 m, at an 85° inclination with 8 benches, with the lowest bench at 6 m). Rock mass quality analysis using Rock Mass Rating (RMR = 78) and Geological Strength Index (GSI = 73), along with Uniaxial Compressive Strength (UCS  40 MPa) tests, supports the recommended mining excavation methods—drill blast for optimizing productivity or the use of a breaker for cost savings.